Fixed Point Theorem of Zamfirescus type in Generalized Cone Metric Spaces - Akinremi, 'Bankole V; Adewale, Olushola kayode (International Journal of Advanced Mathematical Sciences, 2013)
The purpose of this paper is to establish and prove the existence of Zamfirescus fixed point theorem in G-Cone Metric Spaces.The uniqueness is also shown.